MiR-9 is overexpressed in spontaneous canine osteosarcoma and promotes a metastatic phenotype including invasion and migration in osteoblasts and osteosarcoma cell lines. Issue 1 (December 2016) - Fenger, Joelle; Roberts, Ryan; Iwenofu, O.; Bear, Misty; Zhang, Xiaoli; Couto, Jason; Modiano, Jaime; Kisseberth, William; London, Cheryl
Abstract Background MicroRNAs (miRNAs) regulate the expression of networks of genes and their dysregulation is well documented in human malignancies; however, limited information exists regarding the impact of miRNAs on the development and progression of osteosarcoma (OS). Canine OS exhibits clinical and molecular features that closely resemble the corresponding human disease and it is considered a well-established spontaneous animal model to study OS biology. The purpose of this study was to investigate miRNA dysregulation in canine OS. Methods We evaluated miRNA expression in primary canine OS tumors and normal canine osteoblast cells using the nanoString nCounter system. Quantitative PCR was used to validate the nanoString findings and to assess miR-9 expression in canine OS tumors, OS cell lines, and normal osteoblasts. Canine osteoblasts and OS cell lines were stably transduced with pre-miR-9 or anti-miR-9 lentiviral constructs to determine the consequences of miR-9 on cell proliferation, apoptosis, invasion and migration. Proteomic and gene expression profiling of normal canine osteoblasts with enforced miR-9 expression was performed using 2D-DIGE/tandem mass spectrometry and RNA sequencing and changes in protein and mRNA expression were validated with Western blotting and quantitative PCR. OS cell lines were transduced with gelsolin (GSN) shRNAs to investigate the impact of GSN knockdown on OS cell invasion. Results We identified a unique miRNA signature associated with primary canine OS and identified miR-9 as being significantly overexpressed in canine OS tumors and cell lines compared to normal osteoblasts. Additionally, high miR-9 expression was demonstrated in tumor-specific tissue obtained from primary OS tumors. In normal osteoblasts and OS cell lines transduced with miR-9 lentivirus, enhanced invasion and migration were observed, but miR-9 did not affect cell proliferation or apoptosis. Proteomic and transcriptional profiling of normal canine osteoblasts overexpressing miR-9 identified alterations in numerous genes, including upregulation of GSN, an actin filament-severing protein involved in cytoskeletal remodeling. Lastly, stable downregulation of miR-9 in OS cell lines reduced GSN expression with a concomitant decrease in cell invasion and migration; concordantly, cells transduced with GSN shRNA demonstrated decreased invasive properties. Conclusions Our findings demonstrate that miR-9 promotes a metastatic phenotype in normal canine osteoblasts and malignant OS cell lines, and that this is mediated in part by enhanced GSN expression. As such, miR-9 represents a novel target for therapeutic intervention in OS.